Characterizing the local food environment and grocery-store decision making among a large American Indian community in the north-central USA: qualitative results from the Healthy Foods Healthy Families Feasibility Study. Issue 14 (24th May 2019) - Brown, Meagan C; Shrestha, Umit; Huber, Corrine; Best, Lyle G; O'Leary, Marcia; Howard, Barbara; Beresford, Shirley; Fretts, Amanda M
Abstract: Objective: Perceptions of social-contextual food environments and associated factors that influence food purchases are understudied in American Indian (AI) communities. The purpose of the present study was to: (i) understand the perceived local food environment; (ii) investigate social-contextual factors that influence family food-purchasing choices; and (iii) identify diet intervention strategies. Design: This qualitative study consisted of focus groups with primary household shoppers and key-informant interviews with food retailers, local government food assistance programme directors and a dietitian. An inductive, constant comparison approach was used to identify major themes. Setting: A large AI reservation community in the north-central USA. Participants: Four focus groups ( n 31) and seven key-informant interviews were conducted in February and May 2016. Results: Perceptions of both the higher cost of healthy foods and limited access to these foods influenced the types of foods participants purchased. Dependence on government assistance programmes and the timing of benefits also contributed to the types of foods purchased. Participants described purchasing foods based on the dietary needs and preferences of their children. Suggestions for improving the purchase and consumption of healthy foods included: culturally relevant and family-centred cooking classes and workshops focused on monthly food budgeting. Participants also emphasized the importance of involving the entire community in healthy eating initiatives. Conclusions: Cost and access were the major perceived barriers to healthy eating in this large rural AI community. Recommended interventions included: (i) family-friendly and culturally relevant cooking classes; (ii) healthy food-budgeting skills training; and (iii) approaches that engage the entire community.